Revision of Chondrocyclus s.l. (Mollusca: Cyclophoridae), with description of a new genus and twelve new species - Cole, Mary L. (European Journal of Taxonomy, 2019)
Chondrocyclus Ancey, 1898 is a genus of nine species of African operculate land snails restricted to indigenous forest and mesic thicket. Worn specimens (i.e., without a periostracum or operculum), on which some species descriptions and records were based, appear to be indistinguishable morphologically. A comprehensive revision of Chondrocyclus s.l. is provided here based on comparative morphological examinations of the shell, protoconch, periostracum, operculum, radula and penis, and on mitochondrial genes cytochrome c oxidase subunit I and 16S rRNA. Two genus-level lineages are recognised, Chondrocyclus s.s. and Afrocyclus gen. nov. Revised species descriptions are given for seven species. Two species, C. meredithae Bruggen, 1983 and C. chirindae Bruggen, 1986 both from north of South Africa, are removed from Chondrocyclus. Twelve new species are described: C. herberti sp. nov., C. silvicolus sp. nov., C. amathole sp. nov., C. pondoensis sp. nov., C. devilliersi sp. nov., C. pulcherrimus sp. nov., C. cooperae sp. nov., C. langebergensis sp. nov., C. kevincolei sp. nov., A. oxygala gen. et sp. nov., A. potteri gen. et sp. nov. and A. bhaca gen. et sp. nov. This is the first detailed systematic revision of an Afrotropical cyclophorid group to include morphological and molecular data. This study complements research on other taxa of low-vagility forest-dwelling habitat specialists by providing comparative distribution data for an independent, widespread group. Such evidence is urgently needed for conservation of South Africa’s threatened forest biome.